Dysembryoplastic neuroepithelial tumor of cerebellum in a child - Köse, Doğan; Kalkan, Erdal; Paksoy, Yahya; Toy, Hatice; Üçüncü Ergün, Nurcan; Köksal, Yavuz (Kocaeli Derince Education and Research Hospital, 2014)
Dysembryoplastic neuroepithelial tumors are benign neoplasms with typical supratentorial location. 12 year old patient, who applied to a local hospital with complaints of loss of consciousness and postural tonus, was referred to our hospital with cerebellar mass diagnosis. According to the anamnesis, similar complaints also appeared when the patient was 3 and 10 years old, however no anomaly was found in the examinations done by pediatric cardiologist and pediatric neurologist in that period. Physical examination and routine laboratory examinations of the patient were normal. The mass identified in the cerebellum was totally removed. The patient was diagnosed as dysembryoplastic neuroepithelial tumor by histopathological evaluation of the tissue. The patient has still been under outpatient follow-up and in complete remission without any evidence of recurrence for 5 years. In this report a child patient having dysembryoplastic neuroepithelial tumor with cerebellar location is aimed to be shared with the literature.

Disembriyoplastik nöroepitelyial tümörler (DNT) tipik olarak supratentorial yerleşen benign neoplazmalardır. Bilinç ve postural tonus kaybı şikayetleri ile bir lokal hastaneye başvuran 12 yaşındaki erkek hasta saptanan serebellar kitlesi nedeniyle hastanemize refere edildi. Hikayesinden benzer şikayetlerinin 3 ve 10 yaşlarında da tekrar ettiği ancak o dönemde pediatric kardiyolog ve pediatric nörolog tarafından yapılan incelemelerde herhangi bir anomaliye rastlanmadığı öğrenildi. Hastanın fizik muayenesi ve rutin laboratuvar tetkikleri normaldi. Serebellumda saptanan kitle total olarak çıkarıldı. Alınan dokunun histopatolojik değerlendirmesi ile hastaya DNT tanısı konuldu. Hasta halen, 5 yıldır, herhangi bir nüks belirtisi olmadan ayaktan takip edilmektedir. Bu yazıda serebellum yerleşimli DNT'ye sahip bir çocuk vakanın literatürle paylaşılması amaçlanmıştır.
Bir çocukta serebellumun disembriyoplastik nöroepiteliyal tümörü
Keywords: Brain Neoplasms; Benign; Child; Cerebellum; Beyin Neoplazmları; Selim; Çocuk; Serebellum